PHOTOMETRIC RESEARCHES OF ASTEROIDS ON 1.5-M RUSSIAN-TURKISH TELESCOPE - Galeev, A.; Gumerov, R.; Bikmaev, I.; Pinigin, G.; Khamitov, I.; Aslan, Z. (Одеські астрономічні публікації, 2007)
This work describes some research results based on the photometric studies on Russian-Turkish telescope during last five years. During 2004-2006 observations of minor planets were carried out within the international collaboration between Kazan State University, TUBITAK National Observatory and Nikolaev Astronomical Observatory for studying the physical parameters and kinematics of asteroids. As a result the photometric characteristics of these objects have been obtained; the lightcurves frequently demonstrating changes of brightness of these objects caused by their rotation around an axis are constructed. The variability periods and amplitudes for asteroids (762) Pulcova, 2000PN9, (6006) Anaximandros have been found.